Tuning of visible light-driven CO2 reduction and hydrogen evolution activity by using POSS-modified porous organometallic polymers. Issue 31 (7th July 2021) - Wang, Wei-Jia; Chen, Kai-Hong; Yang, Zhi-Wen; Peng, Bo-Wen; He, Liang-Nian
Abstract : Introducing polyhedral oligomeric silsesquioxane (POSS) into Re-based porous organometallic polymers (POMPs) successfully optimizes the POMP morphology and electron transfer efficiency, balancing the CO/H2 molar ratio of the formed syngas. Abstract : Significant efforts have been devoted to the photochemical CO2 reduction reaction (CO2 RR) as a significant pathway for the development of renewable energy systems. However, the competitive hydrogen evolution reaction (HER) greatly impedes the fundamental understanding and industrial application of the CO2 RR. Herein, we report polyhedral oligomeric silsesquioxane (POSS)-based porous organometallic polymers (POMPs) that are able to catalyze the photochemical CO2 RR to produce syngas. Their surface area, CO2 adsorption ability, visible-light harvesting capacity and photoinduced electron–hole separation efficiency can be regulated by tuning the Re-bipyridine content in POMPs. Consequently, the effects of these properties on CO2 RR and HER activities have been investigated and the surface area and electron transfer efficiency of these materials have been elucidated as the key points. Importantly, we also reveal the applicability of the developed strategy in designing new catalysts for the CO2 RR.